2017
DOI: 10.1093/ijlct/ctx017
|View full text |Cite
|
Sign up to set email alerts
|

Materials characterization of innovative composite materials for solar-driven thermochemical heat storage (THS) suitable for building application

Abstract: Thermochemical Heat Storage (THS) systems have recently attracted a lot of attention in research and development. One of the main parameters that influence the performance of a THS system is the thermochemical materials. This paper aims to investigate thermochemical materials which are suitable for both short-term and long-term building heat storage application driven by solar energy for an open system. Innovative composite materials using MgCl2-MgSO4, CaCl2-LiCl and MgSO4- CaCl2 salts mixtures impregnated int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Then the previouslystored thermochemical energy is released. Table 1 Vermiculite-based THS composite energy density and regeneration temperature analysed by SDT-Q600 (Jarimi et al 2017).…”
Section: System Design and Constructionmentioning
confidence: 99%
See 3 more Smart Citations
“…Then the previouslystored thermochemical energy is released. Table 1 Vermiculite-based THS composite energy density and regeneration temperature analysed by SDT-Q600 (Jarimi et al 2017).…”
Section: System Design and Constructionmentioning
confidence: 99%
“…For instance, Casey et al (2015) found vermiculite-CaCl 2 was a promising candidate for open THS systems, which exhibited high heat storage capability and rapid mass uptake at higher relative humidity levels. The characterisation analysis conducted by Jarimi et al (2017) demonstrated the feasibility of using the vermiculite-based composite adsorbents in THS systems. The THS system is still under the research and development stage, which requires more studies on the innovative composite adsorbents and reactor designs (Shen et al, 2021).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…One strategy is to prepare typical selective water sorbents “SWS”, a two-component material based on a porous host matrix with an inorganic salt inside its pores. A series of porous materials are used as the matrix, such as zeolite, , silica gel, , activated alumina, metal–organic framework (MOF), , porous carbon material, porous minerals, , and others. , The salt crystals are dispersed in the pores, and the liquid products can be confined in the pores. However, there is still a problem that salt solution may overflow from the pores when the volume of the solution exceeds the pore volume of the matrixes.…”
Section: Introductionmentioning
confidence: 99%